Targeting SARS‐CoV‐2 by synthetic dual‐acting thiol compounds that inhibit Spike/ACE2 interaction and viral protein production. Issue 2 (30th December 2022) - Fraternale, Alessandra; De Angelis, Marta; De Santis, Riccardo; Amatore, Donatella; Masini, Sofia; Monittola, Francesca; Menotta, Michele; Biancucci, Federica; Bartoccini, Francesca; Retini, Michele; Fiori, Valentina; Fioravanti, Raoul; et al.
Abstract: The SARS‐CoV‐2 life cycle is strictly dependent on the environmental redox state that influences both virus entry and replication. A reducing environment impairs the binding of the spike protein (S) to the angiotensin‐converting enzyme 2 receptor (ACE2), while a highly oxidizing environment is thought to favor S interaction with ACE2. Moreover, SARS‐CoV‐2 interferes with redox homeostasis in infected cells to promote the oxidative folding of its own proteins. Here we demonstrate that synthetic low molecular weight (LMW) monothiol and dithiol compounds induce a redox switch in the S protein receptor binding domain (RBD) toward a more reduced state. Reactive cysteine residue profiling revealed that all the disulfides present in RBD are targets of the thiol compounds. The reduction of disulfides in RBD decreases the binding to ACE2 in a cell‐free system as demonstrated by enzyme‐linked immunosorbent and surface plasmon resonance (SPR) assays. Moreover, LMW thiols interfere with protein oxidative folding and the production of newly synthesized polypeptides in HEK293 cells expressing the S1 and RBD domain, respectively. Based on these results, we hypothesize that these thiol compounds impair both the binding of S protein to its cellular receptor during the early stage of viral infection, as well as viral protein folding/maturation and thus the formation of new viral mature particles. Indeed, all the tested molecules, although at different concentrations, efficiently inhibit both SARS‐CoV‐2 entry and replication in Vero E6 cells. LMW thiols may represent innovative anti‐SARS‐CoV‐2 therapeutics acting directly on viral targets and indirectly by inhibiting cellular functions mandatory for viral replication.